Kinematics Analysis of Synchronized Mobile Steering Mechanism for Dodge Robot - Li Heng; Zheng Meng; He Beilin; Ren Hangfei (Jixie chuandong)
Aiming at the problems of slow movement，poor steering ability and difficult control for the existing robot，a synchronous mobile steering mechanism with clear motion classification and simple structure is designed for dodging robot to realize omni-directional and fast movement in xOy plane. The kinematics principle and the design basis of key parameters of the mechanism are introduced. The steering differential analysis of the mobile mechanism is carried out by using the differential principle，and the kinematics equation. The forward and inverse solutions of the mobile mechanism are obtained. At the same time，the three-dimensional model of the structure is established by UG software. After reasonable simplification，the model is imported into Adams for simulation analysis. The results verify the accuracy of the theoretical design and achieve the desired purpose. It provides an important reference for the design and development of robots.